(−)-Epicatechin improves insulin sensitivity in high fat diet-fed mice - Cremonini, Eleonora (Arch Biochem Biophys, 2016)
Obesity constitutes a major public health concern, being frequently associated with type 2 diabetes (T2D). Evidence from studies in humans and experimental animals suggest that consumption of the flavan-3-ol (−)-epicatechin (EC) and of EC-rich foods may improve insulin sensitivity. To further understand the potential benefits of dietary EC consumption on insulin resistance, this study investigated the capacity of EC supplementation to prevent high fat diet (HFD)-induced insulin resistance in mice. To assess the underlying mechanisms, the effects of HFD and EC consumption on the activation of the insulin cascade and of its negative modulators were evaluated. HFD consumption for 15 w caused obesity and insulin resistance in C57BL/6J mice as evidenced by high fasted and fed plasma glucose and insulin levels, and impaired ITT and GTT tests. This was associated with alterations in the activation of components of the insulin-triggered signaling cascade (insulin receptor, IRS1, ERK1/2, Akt) in adipose and liver tissues. EC supplementation prevented/ameliorated all these parameters. EC acted improving insulin sensitivity in the HFD-fed mice in part through a downregulation of the inhibitory molecules JNK, IKK, PKC and protein tyrosine phosphatase 1B (PTP1B). Thus, the above results suggest that consumption of EC-rich foods could constitute a dietary strategy to mitigate obesity-associated insulin resistance.